On the Controllability for Second Order Hyperbolic Equations in Curved Polygons - Bastos, W.D.; Spezamiglio, A. (Trends in Computational and Applied Mathematics, 2007)
In this work we study exact boundary controllability for a class of hyperbolic linear partial differential equation with constant coefficient which includes the linear Klein-Gordon equation. We consider piecewise smooth domains on the plane, initial state with finite energy and control of Robin type, acting on the whole boundary or only on a part of it.